A Pathway to Circular Economy-Converting Li-Ion Battery Recycling Waste into Graphite/rGO Composite Electrocatalysts for Zinc–Air Batteries - Reio Praats; Jani Sainio; Milla Vikberg; Lassi Klemettinen; Benjamin P. Wilson; Mari Lundström; Ivar Kruusenberg; Kerli Liivand (Batteries)
Li-ion batteries (LIBs) are one of the most deployed energy storage technologies worldwide, providing power for a wide range of applications—from portable electronic devices to electric vehicles (EVs). The growing demand for LIBs, coupled with a shortage of critical battery materials, has prompted the scientific community to seek ways to improve material utilization through the recycling of end-of-life LIBs. While valuable battery metals are already being recycled on an industrial scale, graphite—a material classified as a critical resource—continues to be discarded. In this study, graphite waste recovered from the recycling of LIBs was successfully upcycled into an active graphite/rGO (reduced graphene oxide) composite oxygen electrocatalyst. The precursor graphite for rGO synthesis was also extracted from LIBs. Incorporating rGO into the graphite significantly enhanced the specific surface area and porosity of the resulting composite, facilitating effective doping with residual metals during subsequent nitrogen doping via pyrolysis. These composite catalysts enhanced both the oxygen reduction and oxygen evolution reactions, enabling their use as air electrode catalyst materials in zinc–air batteries (ZABs). The best-performing composite catalyst demonstrated an impressive power density of 100 mW cm−2 and exceptional cycling stability for 137 h. This research further demonstrates the utilization of waste fractions from LIB recycling to drive advancements in energy conversion technologies.